DIGITAL ENTERPRISE MANAGEMENT IN CYBERSPACE - Kurbonov Said Akbarovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article describes the results of a study of cybernetic enterprise management based on the model and technology of digital twin and the concept of IEM (intelligent enterprise managing) system. The digital twin model is a meta-model of a real enterprise and a digital enterprise, that exchange information and informationally interact with each other. Cybernetic management is a stage in the development of digital management. The article formalizes the basic principles of cybernetic management. It is shown, that the “mirroring” technology, borrowed from their theory of database replication, is based on the double enterprise model. This mirroring allows to reflect all real processes in cyberspace. In cyberspace, based on a system of standardized management and standardization rules, optimal production processes are modeled and transferred to a real enterprise. The article describes a virtual conveyor model, that is built as an analogue of value chains. It is shown, that the set of virtual conveyors forms a kind of artificial neural network.